The Depiction of Toxic Masculinity and Its Effects on Children in Hirokazu Koreeda's Monster (2023) - Ainiyah, Syakira Nugraheni (Universitas Negeri Surabaya, 2025)
This study aims to analyze how toxic masculinity is depicted and its impact in the film Monster (2023) by Hirokazu Koreeda, using Michael Kimmel’s theory of masculinity (1997). The method used is qualitative descriptive, with data obtained from scenes and dialogues in the movie, as well as sources such as books, journals, and relevant websites. The results of this study show that this movie depicts various forms of toxic masculinity, such as the demand to be a “real man,” the rejection of anything considered feminine, and homophobia. This has an impact on the psychological condition of the characters Minato and Yori, who experience mental pressure, bullying, and even violence. This study shows how toxic masculinity affects social interactions and reinforces rigid gender norms, especially in children. This study is also expected to contribute to the depiction of toxic masculinity in films and serve as a foundation for further research in the field of gender studies.